The Analysis of Politeness Strategies in Buginese Bone Language - Sunnuraini; Abdul Hakim Yassi (EDUVELOP, 2022)
This study was aimed to investigate the kind politeness strategies used by Buginese Bone in several situations. The source of data was verbal utterances by Buginese Bone. This study used pragmatic study especially theory of politeness by Brown and Levinson. It also used the qualitative descriptive method. The writer used observation by recording and note-taking providing the technique of collecting data. The result of the study showed that the types of politeness strategies used in Buginese Bone are; Negative Politeness, Off-record which found in the interaction between strangers, local inhabitants, family members, superior and subordinate. While, positive politeness is appeared in the interaction between friends. The implication of this research was intended for making good interaction when interacting to other people. The writers also suggest that for further research to investigate the same field in terms of semantics.